Traumatic abdominal intercostal transdiaphragmatic hernia: a case report and literature review - Tang, Hannah N. (International Surgery Journal, 2022)
Abdominal intercostal herniations are a rare entity where abdominal contents herniate through the intercostal space with or without diaphragmatic rupture. Because they are rare, there is little literature to support how they should be treated, conservatively or surgically, and if surgically, what techniques provide the best outcome. This case illustrated the potential for good recovery post-surgical repair of a traumatic intercostal hernia and suggests a guideline used to determine surgical technique.